A national survey of law enforcement post-overdose response efforts. (4th March 2023) - Ray, Bradley; Richardson, Nicholas J.; Attaway, Peyton R.; Smiley-McDonald, Hope M.; Davidson, Pete; Kral, Alex H.
ABSTRACT: Background: Law enforcement agencies in the US have provided naloxone to officers and developed initiatives to follow-up after a non-fatal overdose. However, the prevalence and characteristics of these efforts have yet to be documented in research literature. Objectives: We sought to understand the national prevalence of naloxone provision among law enforcement and examine the implementation of post-overdose follow-up. Methods: We administered a survey on drug overdose response initiatives using a multimodal approach (online and mail) to a nationally representative sample of law enforcement agencies ( N  = 2, 009; 50.1% response rate) drawn from the National Directory of Law Enforcement Administrators database. We further examine a subsample of agencies ( N  = 1, 514) that equipped officers with naloxone who were also asked about post-overdose follow-up. Results: We found 81.7% of agencies reported officers were equipped with naloxone; among these, approximately one-third (30.3%) reported follow-up after an overdose. More than half (56.8%) of agencies indicated partnership in follow-up with emergency medical services as the most common partner (68.8%). There were 21.4% of agencies with a Quick Response Team, a popular national post-overdose model, and were more likely to indicate partnership with a substance use disorder treatment provider than when agencies were asked generally about partners in follow-up (74.5% and 26.2% respectively). Conclusion: Many law enforcement agencies across the US have equipped officers with naloxone, and about one-third of those are conducting follow-up to non-fatal overdose events. Post-overdose follow-up models and practices vary in ways that can influence treatment engagement and minimize harms against persons who use drugs.